Women in Green MSMEs: The Role of Influencers through Digital Marketing - Indra, Indra Permana; Dian, Dian Rachmawati Afadi (Amkop Management Accounting Review (AMAR), 2025)
The objectives of this study are to analyze the role of education and social media on influencers, analyze the role of E-WOW and E-trust on digital marketing, analyze the role of influencers on MSME purchasing decisions, analyze the role of influencers on digital marketing, analyze the role of digital marketing on MSME purchasing decisions, and analyze the role of digital marketing in mediating the relationship between influencers and MSME purchasing decisions. The research data analysis method employs a quantitative descriptive approach, utilizing Structural Equation Modeling (SEM) as the data analysis technique. The research sample consists of women who have transacted with SMEs in the areas of Jakarta, Bekasi City, Bekasi Regency, and Tangerang, who have conducted transactions using e-commerce and other marketplaces. The sampling technique employs interviews, direct observation, and both online and offline questionnaires. The study's results indicate that the direct effect of the education variable has a significant impact on female influencers. Furthermore, the social media variable has a significant influence on female influencers. Additionally, the E-WOM variable has a significant influence on digital marketing. Furthermore, the E-Trust variable has a significant influence on digital marketing. Subsequently, the female influencer variable has a significant influence on the purchasing decisions of SMEs. The results of the female influencer variable do not influence digital marketing. The results of the digital marketing variable have a significant influence on the purchasing decisions of SMEs. However, the digital marketing variable does not mediate the relationship between female influencers and the purchasing decisions of SMEs.